2020
DOI: 10.17140/droj-6-143
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Mechanisms of Allium sativum, Citrus sinensis and Persea americana Extracts: Effects on Inhibition of Digestive Enzymes, Glucose Adsorption and Absorption on Yeast Cells and Psoas Muscles

Abstract: Background Mechanisms by which some plants with antihyperglycemic effects reduce postprandial hyperglycemiaare not fully elucidated. This study was designed to investigate some action mechanisms of extracts from stem bark of Citrus sinensis, seeds of Persea americana and bulbs of Allium sativum including in vitro inhibition of α-amylase and invertase; glucophagic capacity, absorption capacity on yeast cells and psoas tissues. Methods Ethanolic (EE) and aqueous (AE) extracts were tested on α-amylase and inverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Also, they are capable of reducing the secretions and viscosity within the intestinal lumen resulting in preventing or slowing diffusion. Glucose absorbed from the blood might form glycosyl‐flavonoids which are complex molecules formed due to the condensation of flavonoids with hydroxyl groups [44] . The glucose adsorption activity of GAE−CS−TPP nanoparticles (1.20±0.24 mmol/g) was significantly higher than that of G. arborea aqueous extract (−1.11±0.14 mmol/g) at 100 mM glucose concentration (p<0.05) (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they are capable of reducing the secretions and viscosity within the intestinal lumen resulting in preventing or slowing diffusion. Glucose absorbed from the blood might form glycosyl‐flavonoids which are complex molecules formed due to the condensation of flavonoids with hydroxyl groups [44] . The glucose adsorption activity of GAE−CS−TPP nanoparticles (1.20±0.24 mmol/g) was significantly higher than that of G. arborea aqueous extract (−1.11±0.14 mmol/g) at 100 mM glucose concentration (p<0.05) (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose absorbed from the blood might form glycosyl-flavonoids which are complex molecules formed due to the condensation of flavonoids with hydroxyl groups. [44] The glucose adsorption activity of GAEÀ CSÀ TPP nanoparticles (1.20 � 0.24 mmol/g) was significantly higher than that of G. arborea aqueous extract (À 1.11 � 0.14 mmol/g) at 100 mM glucose concentration (p < 0.05) (Figure 7A). However, the adsorption activity of glucose by the aqueous extract of S. pinnata (1.98 mmol/g) was higher than that of SAEÀ CSÀ TPP (1.47 mmol/g) at a glucose concentration of 100 mM (Figure 7B).…”
Section: Glucose Adsorption Activitymentioning
confidence: 95%
“…In addition, the presence of flavonoids and polyphenols in extracts can justify their efficiency as well. These inhibitors, including berberine, are reported to be capable of binding to bind to α‐glucosidase and preventing sucrose fixation (Azantsa et al., 2019; Mojica et al., 2015). The fact that alginate nanoencapsulation could enhance antidiabetic properties with controlled drug release is consistent with the findings of Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
“…The joint action of avocado seeds and garlic aqueous extracts (1:1 w/w) likely reduces body weight (−2.31%) and glycaemia (−27%) compared to atorvastatin ( Fig. 1 ) through mechanisms such as inhibition of digestives enzymes, reduction of intestinal bioavailability of glucose, reduction of glucose absorption, and increase glucose uptake by muscles via enhanced insulin action as demonstrated by Azantsa et al [ 15 , 37 ].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies demonstrated that seeds of avocado and garlic are great sources of antioxidants, and are capable of scavenging free radicals or preventing their generation [ 15 , 36 ] . Persea americana seeds and Allium sativum extracts possess anti-hemolytic and anti-lipid peroxidation effects which contribute to improve oxidative status of animals [ 37 ]. In fact, flavonoids from both plants induce suppression of RONS generation, inhibit enzymes or chelate trace elements involved in free radical formation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%